Delimitation of loss of productivity claims or disruptions in Public Construction Contract - Collantes Rojas, Christian (2020)
In this paper, the author identifies the legal devices within the Peruvian legal system that allow the acceptance of a claim and acceptance for loss of productivity or disruptions in public construction contract, under the Public Procurement Law. This, in the framework of an arbitration in which a party is a Public Administration Entity. For this, the author makes a roadmap of a claim for loss of productivity, what is disruption, what is not disruption, how to properly quantify it and, finally, what legal tools of our legal system allow its acceptance.